A novel freeze-dried natural microalga powder for highly efficient removal of uranium from wastewater. (November 2021) - Cheng, Yanxia; Li, Feize; Liu, Ning; Lan, Tu; Yang, Yuanyou; Zhang, Ting; Liao, Jiali; Qing, Renwei
Abstract: It is of great significance to develop convenient methods and low-cost materials to remove uranium from wastewater. Ankistrodesmus sp., an easy growing green alga, was employed for highly efficient removal of uranium from aqueous solution. The biosorption results under different experimental condition indicate that the alga possess outstanding uranium adsorption ability ( q max  = 601.2 mg g −1 ). Moreover, Ankistrodesmus sp . could be effectively regenerated with hydrochloric acid solution (0.1 M) and used again for uranium adsorption. Even in simulated mine water with various coexisting ions, Ankistrodesmus sp . also exhibits high removal efficiency (95.6%) towards uranium. Furthermore, the adsorption behavior of uranium by alga could be described in the Freundlich isotherms model and the adsorption process was consistent with the pseudo-second-order kinetics model. The characteristic of Fourier transform infrared spectrum, scanning electron microscopy, transmission electron microscope and X-ray photoelectron spectroscopy reveal that –NH2, –COOH, –CONH2 and C–O groups have participated in biosorption process. Therefore, complexation, electrostatic adsorption and ions exchange are the dominated action of uranium biosorption in the algae. All findings in this work suggest that Ankistrodesmus sp . can be a promising candidate for the effective and practical application in field of disposed uranium contamination. Graphical abstract: Image 1 Highlights: Ankistrodesmus sp. is employed to remove uranium for the first time. The q max of Ankistrodesmus sp. is as high as 601.2 mg g −1 . The algae display excellent removal efficiency from simulated mine wastewater. Ankistrodesmus sp. has been demonstrated to be affordable and reusable biosorption material.